Contemporary tourist behaviour yourself and others as tourists - Bowen, David (Of Oxford Brookes Business School) (Oxfordshire, UK Boston, MA CABI, 2022)
"Providing a cross-disciplinary approach to tourism behaviour, this fully updated edition responds to new emerging themes such as the digital revolution, social media, and tourist-risk resulting from political instability and other uncertainty. With international examples throughout, this new edition reviews both theory and practical application"--
Backdrop -- Frameworks, models and theories -- Family, friends and groups -- Gender, religion and race -- Technological change -- Ethical consumption -- Motivation -- Fear -- Information search and decision-making -- Image and decision making -- In-visit experience -- Satisfaction: fulfilling the promise -- Life change: tourist experience and beyond -- Final word.
Includes bibliographical references and index.
Keywords: Consumer behavior; Tourism -- Social aspects; Tourists -- Psychology